Optimalisasi Literasi Digital dan Komunikasi Ilmiah Mahasiswa melalui Pelatihan Video Proposal Penelitian Berbasis Renderforest - Mutiara Yunita Harahap; Wiki Tedi Rahmawati; Putra Thoip Nasution; Syifa Dhawiyah Wijaya; Nesha Putri Fadillah (Fakultas Keguruan dan Ilmu Pendidikan UNIVA Medan, 2026)
Digital literacy and scientific communication are essential skills that students must master to meet academic demands, adapt to technological developments, and compete in the professional world. One common challenge is how students can present their research proposals in an engaging, structured, and communicative way that is easily understood by lecturers and a wider audience. To address this need, a community service program was conducted through training on the use of Renderforest as a medium for creating research proposal video presentations. The program included several stages: socialization on the importance of digital literacy, demonstration of Renderforest features, hands-on video production practice, and intensive mentoring until students were able to produce their final projects independently. The results showed significant improvement in students’ ability to manage visual content, select appropriate templates, organize the flow of scientific presentations, and integrate narration with multimedia elements. Overall, this training made a tangible contribution to enhancing students’ digital literacy, creativity, and scientific communication skills, while also fostering their confidence in presenting research ideas professionally and attractively.